2012
DOI: 10.1038/labinvest.2012.76
|View full text |Cite
|
Sign up to set email alerts
|

Estriol preserves synaptic transmission in the hippocampus during autoimmune demyelinating disease

Abstract: Cognitive deficits occur in over half of multiple sclerosis patients, with hippocampal-dependent learning and memory commonly impaired. Data from in vivo MRI and post-mortem studies in MS indicate that the hippocampus is targeted. However, the relationship between structural pathology and dysfunction of the hippocampus in MS remains unclear. Hippocampal neuropathology also occurs in experimental autoimmune encephalomyelitis (EAE), the most commonly used animal model of MS. Although estrogen treatment of EAE ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 74 publications
2
37
0
2
Order By: Relevance
“…Therefore, we hypothesize that the relatively modest effect on localized GM sparing using VBM may be due to a lack of direct neuroprotective effects of natalizumab. Estrogens, in contrast, have been shown to be neuroprotective in a variety of neurologic disease models (Bode et al., 2008; Engler‐Chiurazzi, Brown, Povroznik, & Simpkins, 2017; Spence & Voskuhl, 2012; Suzuki, Brown, & Wise, 2009), including estriol treatment on cognitive electrophysiologic and neuropathologic outcomes in the MS model (Ziehn, Avedisian, Dervin, O'Dell, & Voskuhl, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesize that the relatively modest effect on localized GM sparing using VBM may be due to a lack of direct neuroprotective effects of natalizumab. Estrogens, in contrast, have been shown to be neuroprotective in a variety of neurologic disease models (Bode et al., 2008; Engler‐Chiurazzi, Brown, Povroznik, & Simpkins, 2017; Spence & Voskuhl, 2012; Suzuki, Brown, & Wise, 2009), including estriol treatment on cognitive electrophysiologic and neuropathologic outcomes in the MS model (Ziehn, Avedisian, Dervin, O'Dell, & Voskuhl, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…While the protective effect of estriol treatment on MS appears to be mediated in part by anti‐inflammatory mechanisms (Gold et al., 2009; Soldan, Alvarez Retuerto, Sicotte, & Voskuhl, 2003; Voskuhl & Gold, 2012), this is not mutually exclusive of direct neuroprotective effects, as these have been shown in the MS model (Crawford et al., 2010; Kim et al., 2018; MacKenzie‐Graham et al., 2012; Spence et al., 2011). Together, preclinical data in EAE have shown that estriol is acting to decrease microglial activation, induce remyelination, and increase synaptic plasticity (Kim et al., 2018; Ziehn et al., 2012). Further, we have shown that treatment with estrogens and estrogen receptor ligands prevented both cortical and cerebellar GM atrophy by MRI, which correlated with preserving axons, neurons, and synapses in EAE (Itoh et al., 2017; Kim et al., 2018; MacKenzie‐Graham et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the literature on the origins of sex-biased neurological diseases has focused on the role of sex steroid hormones, particularly the role of estrogen and testosterone in neuroprotection (20,21,(25)(26)(27)(28). The increased female bias for MS could theoretically result from deleterious effects of physiologic levels of female sex hormones or protective effects of male sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In addition, oestrogen treatment improves cognitive dysfunction in women without multiple sclerosis who have had ovariectomy, 36 and oestrogen treatment of ovariectomised animals increases dendritic spines and synapses in cerebral grey matter. [37][38][39] We showed that higher serum estriol concentrations might be needed for benefi cial eff ects on cognition. Cortical grey matter sparing in the estriol group compared with the placebo group was lost at 24 months, when both estriol concentrations and PASAT scores had decreased.…”
Section: All Patientsmentioning
confidence: 97%